A Low Power CMOS UWB LNA with Sub-1V Supply Voltage and Noise Cancellation Technique - Mehdi Alinejad; Emad Ebrahimi (مجله مدل سازی در مهندسی)
Low noise amplifiers (LNA) in RF receivers are usually the first block after the antenna that amplify the signal received from the antenna with negligible noise and distortion. The most important desirable characteristics of an LNA are relatively high gain, low power consumption, appropriate matching of input and output impedance, and low noise figure. Using the noise cancelation method, the design and simulation of a new wideband LNA has been discussed in this paper, in which the power consumption has been significantly reduced by using positive feedback as well as sub-1 volt supply voltage. First, the proposed circuit was analyzed in this article. Then, the proposed amplifier has been implemented in TSMC 0.18µm RF-CMOS technology and simulated using Cadence-IC software. The simulations show that the noise figure of this structure has improved by about 2dB compared to the conventional structure, and its noise figure has reached 3.6dB to 4.5dB in the frequency range of 2GHz to 12GHz. The maximum gain of the LNA is 17.25dB, and its S11 and S22 parameters are less than -9.24dB and -9.74dB, respectively. S12 is also less than -28.5dB. The linearity of this amplifier in term of IIP3 is -3.42dBm. The total power consumption of the circuit is 4.89mW with a supply voltage of 0.8V that results in 70% power consumption reduction. According to the physical layout the circuit occupies only 0.89 mm2 of active area..